Digital interventions to moderate alcohol consumption in young people: a Cancer Prevention Europe overview of systematic reviews - McDermott, Kevin T.; Noake, Caro; Wolff, Robert; Espina, Carolina; Foucaud, Jérôme; Steindorf, Karen; Schüz, Joachim; Thorat, Mangesh A.; Weijenberg, Matty; Bauld, Linda; Kleijnen, Jos (Frontiers in Digital Health, 2023)
Background Strategies to reduce alcohol consumption would contribute to substantial health benefits in the population, including reducing cancer risk. The increasing accessibility and applicability of digital technologies make these powerful tools suitable to facilitate changes in behaviour in young people which could then translate into both immediate and long-term improvements to public health. Objective We conducted a review of systematic reviews to assess the available evidence on digital interventions aimed at reducing alcohol consumption in sub-populations of young people [school-aged children, college/university students, young adults only (over 18 years) and both adolescent and young adults (<25 years)]. Methods Searches were conducted across relevant databases including KSR Evidence, Cochrane Database of Systematic Reviews (CDSR) and Database of Abstracts of Reviews of Effects (DARE). Records were independently screened by title and abstract and those that met inclusion criteria were obtained for full text screening by two reviewers. Risk of bias (RoB) was assessed with the ROBIS checklist. We employed a narrative analysis. Results Twenty-seven systematic reviews were included that addressed relevant interventions in one or more of the sub-populations, but those reviews were mostly assessed as low quality. Definitions of “digital intervention” greatly varied across systematic reviews. Available evidence was limited both by sub-population and type of intervention. No reviews reported cancer incidence or influence on cancer related outcomes. In school-aged children eHealth multiple health behaviour change interventions delivered through a variety of digital methods were not effective in preventing or reducing alcohol consumption with no effect on the prevalence of alcohol use [Odds Ratio (OR) = 1.13, 95% CI: 0.95–1.36, review rated low RoB, minimal heterogeneity]. While in adolescents and/or young adults who were identified as risky drinkers, the use of computer or mobile device-based interventions resulted in reduced alcohol consumption when comparing the digital intervention with no/minimal intervention (−13.4 g/week, 95% CI: −19.3 to −7.6, review rated low RoB, moderate to substantial heterogeneity).In University/College students, a range of E-interventions reduced the number of drinks consumed per week compared to assessment only controls although the overall effect was small [standardised mean difference (SMD): −0.15, 95% CI: −0.21 to −0.09]. Web-based personalised feedback interventions demonstrated a small to medium effect on alcohol consumption (SMD: −0.19, 95% CI: −0.27 to −0.11) (review rated high RoB, minimal heterogeneity). In risky drinkers, stand-alone Computerized interventions reduced short (SMD: −0.17, 95% CI: −0.27 to −0.08) and long term (SMD: −0.17, 95% CI: −0.30 to −0.04) alcohol consumption compared to no intervention, while a small effect (SMD: −0.15, 95% CI: −0.25 to −0.06) in favour of computerised assessment and feedback vs. assessment only was observed. No short-term (SMD: −0.10, 95% CI: −0.30 to 0.11) or long-term effect (SMD: −0.11, 95% CI: −0.53 to 0.32) was demonstrated for computerised brief interventions when compared to counsellor based interventions (review rated low RoB, minimal to considerable heterogeneity). In young adults and adolescents, SMS-based interventions did not significantly reduce the quantity of drinks per occasion from baseline (SMD: 0.28, 95% CI: −0.02 to 0.58) or the average number of standard glasses per week (SMD: −0.05, 95% CI: −0.15 to 0.05) but increased the risk of binge drinking episodes (OR = 2.45, 95% CI: 1.32–4.53, review rated high RoB; minimal to substantial heterogeneity). For all results, interpretation has limitations in terms of risk of bias and heterogeneity. Conclusions Limited evidence suggests some potential for digital interventions, particularly those with feedback, in reducing alcohol consumption in certain sub-populations of younger people. However, this effect is often small, inconsistent or diminishes when only methodologically robust evidence is considered. There is no systematic review evidence that digital interventions reduce cancer incidence through alcohol moderation in young people. To reduce alcohol consumption, a major cancer risk factor, further methodologically robust research is warranted to explore the full potential of digital interventions and to form the basis of evidence based public health initiatives.